VD_FINDINFO AI 40/11 - 89/2012 vom 13. Februar 2012 - VD Tribunal cantonal (2012)
LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, DROIT À LA PRESTATION D'ASSURANCE, DÉBUT | 28 al. 1 LAI, 29 al. 1 LAI, 6 LPGA, 7 LPGA, 8 LPGA